Hubungan Asupan Zat Besi, Vitamin C dan Status Gizi dengan Kadar Hemoglobin Pada Remaja Putri Kelas X di SMA Negeri 1 Teras Kabupaten Boyolali - Tiastuti, Santi Ermin; , Siti Zulaekah, A., M.Si; , Dr. Listiana D. S., M.Si (2016)
Intake of Iron and Vitamin C affects hemoglobin levels. Hemoglobin is a parameter used to establish the prevalence of anemia. Low levels of hemoglobin in the blood can be caused by to low intake of iron rich foods, it can be also caused by the consumption of food with low biovaibilits result in small amount of iron absorbed in the body.To determine the association of the intake of iron, vitamin C and nutritional status to hemoglobin levels in SMAN 1 Teras Boyolali.This observational research with cross sectional approach. A total of 63 people were recrulted using simple random sampling according to the inclusion criteria. The data of iron and vitamin Cintake was obtained using Food Record. Nutritional status data was obtained by measuring the weight and height of the subjects Hemoglobin levels were measured using the Chyanmeth Hemoglobin method. The statistical test used was Pearson product moment and Spearman Rank.63,64% and 62,12% of the subjects have low intake of iron and vitamin C respetively. 83,3% of the subjects have normal nutritional status. There is anassociation betweeniron and vitamin C intake with hemoglobin levels (p = 0.0001). No association between nutritional status and hemoglobin levels (p = 0,339).There is a relationship between were found iron and vitamin C intake and hemoglobin levelno association between niutritional status and hemoglobin levels were found.